Intuition beyond recognition: when less familiar events are liked more - Betsch, Tilmann; Hoffmann, Katja; Hoffrage, Ulrich; Plessner, Henning (Experimental psychology, 2003)
In a laboratory experiment, we compare the relative impact of two possible determinants of intuitive evaluative judgments: ease of recognition and total value of prior encounters with a target. Participants encode daily return values of shares on the stock market while watching videotaped ads on the computer screen. This dual-task procedure ensures that participants subsequently lack relevant event memories and thus have to rely on their intuition when evaluating the targets. In the presentation, the share appearing least frequently produced the highest sum of returns. In contrast, the share appearing most frequently produced the lowest sum of returns. Evaluative judgments reveal a preference for the share with the highest sum of returns, although, as evident from recognition latencies, it was the one that was more difficult to recognize. The results provide evidence for the value-account model of implicit attitude formation (Betsch, Plessner, Schwieren, & Gütig, 2001), which predicts that intuitive evaluative judgments reflect the total value of prior encounters.
Online veröffentlicht: September 01, 2006
Gesehen am 21.07.2022